PENGARUH PENGGUNAAN MEDIA FILM DOKUMENTER HARUN YAHYA TERHADAP HASIL BELAJAR IPA SISWA KELAS X SMK N 1 GUGUK - SRI MAIYENA (Ta'dib, 2014)
This research was aimed to know the effect of using documentary film on the tenth grade students’ achievement of SMKN 1 Guguk. The design of the research was randomized control group only design. The population of the research was all of the tenth grade students of SMKN 1 Guguk who were registered in 2010/2011 academic year. The sample of the research was chosen by using purposive random sampling technique in which Contruction class was as control group and Electronic was as experimental group. After analyzing the data, it could be concluded that there was an effect of using documentary film on the tenth grade students’ achievement of SMKN 1 Guguk.Kata kunci: media film documenter Harun Yahya, pembelajaran IPA kelas X SMK, hasil belajar